Factors Influencing the Airport Customer Experience: A Case Study of Auckland International Airport's Customers - Losekoot, Erwin (Auckland University of Technology, 2015)
The aim of this study was to investigate the factors influencing the airport customer experience. Much current research and management effort on airports focuses on efficiency, effectiveness, speed of processing and rankings on international league tables. These measures seem to reward those airports which can best move the largest number of passengers and their luggage. The writer of this study believed that the ‘experience’ of the ‘airport customer’ (passengers and those meeting or farewelling them) is not being given sufficient prominence at a time when it is recognised that the ‘experience economy’ can add value and create customer loyalty. New Zealand’s largest airport was the case study location for this research, and 120 interviews were undertaken in the airport environment with people who were experiencing the airport, either as arriving or departing passengers, or those greeting or farewelling them. In addition, 10 interviews were undertaken with airport management to explore their perceptions of the airport customer experience. All interviews with airport customers were undertaken in the land-side food court area of the international terminal. A plan of the airport is provided in Appendix 2 to assist the reader in understanding the layout of the airport. The guided conversations were focused on encouraging participants to share their perspective of the airport customer experience in order to build on what is already known from the quantitative surveys of passengers which are the more common form of research into airports. Together with the above data, the writer also kept a detailed research diary with observations made over the course of the data gathering phase. Hermeneutics guided the interpretive process which resulted in a number of overarching themes or notions which form the basis of this study’s findings. These include processes, people, physical environment and ‘placeness’. However, the research also uncovered what the writer has termed a ‘personal travel philosophy’. There was a significant number of people who, despite delays and other obstacles to their travel plans, appeared to be remarkably content with their lot at the airport, and this term is used to describe that group. The research concludes with a proposed model of the airport customer experience addressing five aspects – physical environment, processing, people, placeness and personal travel philosophy – and provides recommendations for airport management and opportunities for further academic research both in airports and in congruous areas such as hospitals. Airport management must spend time making people feel welcome if these spaces are to be perceived as hospitable places. The contribution that this thesis makes to the body of knowledge is a deeper understanding of the factors influencing the airport customer experience in the customers’ own words. It allows the voices of airport customers to be heard in a way that has not previously happened, in part because the dominant paradigm is a positivist one of facts, figures, benchmarks and league tables. By taking the time to listen carefully in an open-ended discussion, this research has identified much of what the airport customer really feels about the space they are obliged to spend an increasing amount of time in.
Keywords: Airport; Customer; Experience; Hermeneutic; Phenomenology; Heidegger; Auckland; New Zealand